The Relationship between Disaster Knowledge and Disaster Preparedness Attitudes in Medical Students of Universitas Negeri Gorontalo - Andhika Rezeky Gunawan Gani; Zuhriana K Yusuf; Irmawati Irmawati (Jambura Medical and Health Science Journal, 2023)
Introduction: The incidence of natural disasters worldwide is increasing and unpredictable. As one of the high-risk disaster countries, good knowledge and disaster preparedness in Indonesia residence are needed to reduce the risk of a disaster. As agents of change, students should have competent skills in disaster situations. This study aims to determine the relationship between disaster knowledge and disaster preparedness attitudes among medical students at Universitas Negeri Gorontalo (UNG).Method: This research is a descriptive study with a cross-sectional design and uses a total sampling technique on active UNG medical students during the research period. The research was conducted at the UNG Faculty of Medicine from September to November 2022. The research instrument used a questionnaire that had been used in previous studies. The independent variable is disaster knowledge, while the dependent variable is disaster preparedness attitudes. Bivariate analysis was carried out using the chi-square test to determine the relationship between the two variables.Results: Of the 208 respondents, most have a high level of disaster knowledge of 81.7%. The description of disaster preparedness attitudes shows that most respondents have a good attitude towards disaster preparedness, namely 52.4%. There is no significant relationship between disaster knowledge and preparedness attitudes (p-value 0.160).Conclusion: There is no relationship between disaster knowledge and disaster preparedness attitudes among UNG medical students. It is hoped that the institution will continue to develop disaster education so that students can have better disaster knowledge and be able to deal with disaster situations. Key words: Attitude, disaster, knowledge, preparedness